2014
DOI: 10.1073/pnas.1416247111
|View full text |Cite
|
Sign up to set email alerts
|

Dendrites are dispensable for basic motoneuron function but essential for fine tuning of behavior

Abstract: Dendrites are highly complex 3D structures that define neuronal morphology and connectivity and are the predominant sites for synaptic input. Defects in dendritic structure are highly consistent correlates of brain diseases. However, the precise consequences of dendritic structure defects for neuronal function and behavioral performance remain unknown. Here we probe dendritic function by using genetic tools to selectively abolish dendrites in identified Drosophila wing motoneurons without affecting other neuro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 44 publications
1
19
0
Order By: Relevance
“…In agreement with findings that basic flight motoneuron function is retained even with a minimal set of dendrites (Ryglewski et al, 2014b), intra-neuronal dendrite shifts as caused by either Rdl or nAChR overexpression did not alter firing rates or wingbeat frequencies during tethered flight. By contrast, adaptive adjustments of motoneuron firing frequencies in response to visual input during flight behavior were impaired.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In agreement with findings that basic flight motoneuron function is retained even with a minimal set of dendrites (Ryglewski et al, 2014b), intra-neuronal dendrite shifts as caused by either Rdl or nAChR overexpression did not alter firing rates or wingbeat frequencies during tethered flight. By contrast, adaptive adjustments of motoneuron firing frequencies in response to visual input during flight behavior were impaired.…”
Section: Discussionsupporting
confidence: 90%
“…If GABAergic and cholinergic synaptic inputs competed for a given amount of available dendrites via locally restricted Ca 2+ -dependent mechanisms, one has to postulate that activation of the Rdl GABA A Rs also causes local dendritic Ca 2+ influx. Paradoxically, in insect neurons, including adult Drosophila (Ryglewski et al, 2014b), chloride influx through GABA A Rs is inhibitory and hyperpolarizing relative to resting. Therefore, at first, local dendritic Ca 2+ influx did not seem reconcilable with Rdl receptor activation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our data are consistent with research in monkey inferotemporal cortex, which is the proposed homolog of human VTC, where anatomical development is characterized by a prolific generation of dendritic spines and a doubling in size of dendritic arbors (7). The growth of dendritic arbors may impact the spatial extent from which pyramidal neurons pool information (13, 14) and the spatial extent of lateral inhibition (12), both of which could enhance functional selectivity. Another source of tissue development may be developmental increases in oligodendrocytes and myelination (1517), which are thought to depend on neural function (18).…”
mentioning
confidence: 99%
“…However, recent studies in the stomatogastric ganglion of crabs showed that the specific tapering of dendritic branches can effectively compact elaborate dendritic structures to a uniform electrotonic compartment, thus strongly reducing the impact of synapse positioning along a dendritic arbor on signal integration and ultimately spike output 6466 . Conversely, experimentally reduced dendritic arbor complexity of Drosophila flight motorneurons still supports astonishingly normal neuronal performance, and only behaviors requiring fine precision appear to be negatively affected 67 . Here we show that a drastic increase in dendritic arbor size, and numbers of synaptic connections, as caused by pan-neuronal abrogation of Jeb-Alk signaling (Fig 4 and 5) did not produce noticeable motor defects.…”
Section: Discussionmentioning
confidence: 99%